Menakar Budaya, Meramu Dogma: Sumbangan Nilai Budaya Bagi Dogma Gereja - Salabay, Nita Abia; Batlajery, Agustinus Marthinus Luther (Indonesian Journal of Theology, 2025)
Igya Ser Hanjob is a tradition of the Arfak tribe in the Arfak Mountains of West Papua that emphasizes the importance of maintaining boundaries in forest use to ensure environmental sustainability. However, external influences such as government and corporate entities have undermined these values, resulting in forest degradation and the loss of indigenous authority. The Evangelical Christian Church in West Papua/Gereja Kristen Injili di Tanah Papua (GKI-TP), which plays an important role in maintaining and re-teaching these values, must change its anthropocentric approach to better support ecological balance and environmental sustainability. Through the method of dogmatics in ecclesiological perspective, we place into integrative dialogue the ecological values presented in Igya Ser Hanjob and the church’s teachings. In doing so, we argue that the ecological damage in the provincial capital, Manokwari, can be mitigated and even anticipated by retrieving the values of Igya Ser Hanjob. This local wisdom serves not only as a conservation concept but also as a contribution to a contextual eco-ecclesiological doctrine for the church (GKI-TP) and the contemporary Arfak indigenous community.